Influence of various energy sources in rations on fattening performance and profitability in yearling lambs - Atalay, AI; Tosun, R (Journal of the Hellenic Veterinary Medical Society, 2025)
The aim of this study was to determine the effects of rations created with different energy sources on the fattening performance and economic profit of male yearling lamb rations. The energy sources of the rations used in the study were barley (Experiment-1), wheat (Experiment -2), and corn (Experiment -3). The animal material of the study consisted of male yearlings lambs of the Morkaraman breed, aged 7.5-8 months and with an average body weight of 44 kg.. The study consisted of 27 animals in total, 9 animals in each group, with 3 replications and 3 animals in each replication. In the study, male yearlings lambs were subjected to a 56-day fattening trial. At the end of the experiment, significant differences were found among the groups in terms of body weight, avarage daily gain, feed intake, and feed conversion ratio (P<0.05). The experiment-2 group had the highest body weight, avarage daily gain, and feed intake during the entire fattening period. The experiment-1 and especially experiment-2 groups performed well during the first 28 days of the fattening research. Experiment-2 performed the best in terms of feed conversion ratio, followed by experiment-1 and experiment-3. Between the 29-56th days of the fattening period, the experiment-3 groups performance improved. On the other hand, it was determined that the performance of experiment-1 and experiment-2 decreased between 29-56 days of the fattening period compared to 0-28 days. When the cost of the 1 kg ration used in the research was examined, it was determined that the lowest cost ration belonged to experiment-3, and experiment-1 and experiment-2 were the same. Parallel to the ration costs, it was determined that the lowest cost per 1 kg of body weight gain was in experiment-3, while the highest cost was in experiment-1. However, when examining both the income and profit from body weight gain, they determined that experiment-2 was significantly better than the other groups. In conclusion, the best performance and economic gain in male yearlings lambs fed with rations composed of different energy sources were obtained from wheat-based rations.